Reliability Evaluation of Wind Turbine Systems’ Components - Seyed Mohsen Miryousefi Aval; Amir Ahadi (Bulletin of Electrical Engineering and Informatics, 2016)
The increasing use of wind generation requests modifications in the electric power systems planning conception, because it includes one more uncertainty component, which needs to be studied properly and modeled. Understanding the failures rates and downtimes of wind turbines is difficult not only because of the considerable range of designs and sizes that are now in service worldwide but also since studies are conducted independently under various operating conditions in different countries. The fault tree method (FTA) has been used to study the reliability of many different power generation systems. This paper now applies that method to a wind turbine system to estimate the reliability of wind turbines. In the implementations, several types of wind turbines were considered in order to analyze the system’s reliability. The effectiveness of the proposed method is revealed through several case studies.